Review of "Holding Up the Sky," or Naming Maine as Wabanaki Homelands - Jess L. Cowing (Disability Studies Quarterly, 2022)
No abstract available.
Keywords: settler ableism; disability justice; Indigeneity; interdependence; self-determination; collective care; language reclamation; Wabanaki